resolva as seguintes equações exponenciais:
f(x) 1/4 elevado -1
f(x) 1/4 elevado 1
f(x) 1/4 elevado 2
Respostas
respondido por:
2
f(x)=![( \frac{1}{4}) ^{-1} = \frac{4}{1} =4 ( \frac{1}{4}) ^{-1} = \frac{4}{1} =4](https://tex.z-dn.net/?f=%28+%5Cfrac%7B1%7D%7B4%7D%29+%5E%7B-1%7D++%3D+%5Cfrac%7B4%7D%7B1%7D+%3D4)
f(x)=![( \frac{1}{4} ) ^{1} = \frac{1}{4} ( \frac{1}{4} ) ^{1} = \frac{1}{4}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B1%7D%7B4%7D+%29+%5E%7B1%7D+%3D+%5Cfrac%7B1%7D%7B4%7D+)
f(x)=
f(x)=
f(x)=
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás